The Prognosis of Breast Cancer Patients after Mastectomy and Immediate Breast Reconstruction: A Meta-Analysis - Yang, Xue (PLoS One, 2015)
BACKGROUND: An increasing number of patients with breast cancer are being offered immediate breast reconstruction (IBR). The aim of this study was to analyze the impact of IBR on the prognosis of patients with breast cancer. METHODS: We searched the electronic databases of Medline (Pubmed), ISI Web of Knowledge, Embase, and Google Scholar databases for studies reporting the overall recurrence, disease-free survival (DFS), and overall survival (OS) of patients after mastectomy only and mastectomy with IBR. With these data, we conducted a meta-analysis of the clinical outcomes. RESULTS: Fourteen studies, including 3641 cases and 9462 controls, matched our criteria. Relevant information was extracted from these 14 studies. There was no significant heterogeneity (P for Q-statistic > 0.10 and I(2) < 25%). Patients who underwent IBR showed no increased risk of overall recurrence of breast cancer (RR = 0.89; 95% confidence interval [CI]: 0.75, 1.04; P = 0.14). Furthermore, patients receiving IBR had similar DFS (RR = 1.04; 95%CI: 0.99, 1.08); P = 0.10) and OS (RR = 1.02; 95%CI: 0.99, 1.05; P = 0.24)) as those of control patients. CONCLUSION: This meta-analysis provides evidence that IBR does not have an adverse effect on prognosis. These data suggest that IBR is an appropriate and safe choice for patients with breast cancer.